Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1093/glycob/10.8.815
|View full text |Cite
|
Sign up to set email alerts
|

The heterodimeric structure of glucosidase II is required for its activity, solubility, and localization in vivo

Abstract: Glucosidase II is an ER heterodimeric enzyme that cleaves sequentially the two innermost alpha-1,3-linked glucose residues from N-linked oligosaccharides on nascent glycoproteins. This processing allows the binding and release of monoglucosylated (Glc(1)Man(9)GlcNAc(2)) glycoproteins with calnexin and calreticulin, the lectin-like chaperones of the endoplasmic reticulum. We have isolated two cDNA isoforms of the human alpha subunit (alpha1 and alpha2) differing by a 66 bp stretch, and a cDNA for the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 46 publications
5
94
0
Order By: Relevance
“…Gls2p Localization Is Unaffected in ⌬gtb1 Cells-It has been suggested that GII␤ may contribute to the stability and/or ER retention of GII␣ in mammalian cells (11,12). We therefore further examined the expression of Gls2p in ⌬gtb1 cells.…”
Section: Gtb1 Encodes the Yeast Homologue Of Gii␤-there Is A Singlementioning
confidence: 99%
“…Gls2p Localization Is Unaffected in ⌬gtb1 Cells-It has been suggested that GII␤ may contribute to the stability and/or ER retention of GII␣ in mammalian cells (11,12). We therefore further examined the expression of Gls2p in ⌬gtb1 cells.…”
Section: Gtb1 Encodes the Yeast Homologue Of Gii␤-there Is A Singlementioning
confidence: 99%
“…Mammalian glucosidase II consists of a catalytic ␣ subunit and a 58 kDa ␤ subunit that localizes the enzyme to the ER (Trombetta et al, 1996;Pelletier et al, 2000). Although a ␤ subunit has recently been identified in yeast as well, it is not required for localization of Rot2p (Wilkinson et al, 2006).…”
Section: Journal Of Cell Science 119 (22)mentioning
confidence: 99%
“…Briefly, newly synthesized N-linked glycoproteins are glycosylated with 14 sugars donated from a dolichol-linked lipid via oligosaccharyl transferase (Das and Heath 1980). Following the sequential removal of the terminal glucose by glucosidase I (Hettkamp et al 1984;Bause et al 1989), the glycoprotein may then be recognized by the protein malectin (Schallus et al 2008;Chen et al 2011;Galli et al 2011), potentially for presentation to glucosidase II for removal of the second glucose residue (Burns and Touster 1982;Reitman et al 1982;Pelletier et al 2000). The resulting mono-glucosylated glycoprotein is then a client for association with calnexin or calreticulin (Hammond et al 1994;Zapun et al 1997;Schrag et al 2003).…”
Section: The Calnexin Cycle As Extended Er Microdomainsmentioning
confidence: 99%